CACAHSEWU: Exploration of Batik Obor Sewu as an Ethnomathematics Learning Media for Whole Numbers Material in Grade IV Elementary School - Siska Aprilia; Ari Metalin Ika Puspita; Nadi Suprapto (Papanda Publisher, 2026)
This research aims to explore mathematical concepts in Batik Obor Sewu of the Samin community in Bojonegoro and implement them in teaching addition and subtraction operations of whole numbers in grade IV at SD Negeri Mayangkawis II. This study employs a qualitative approach with ethnographic methods for cultural exploration, followed by implementation of the CACAHSEWU worksheet based on ethnomathematics. Data collection was conducted through interviews with community leaders (Samin descendants) and batik artisans from the Samin community, learning observations, documentation, and analysis of student work. The results show that Batik Obor Sewu contains mathematical concepts such as repeating patterns, numbers, arithmetic operations, measurement, and economic transactions that can be integrated into elementary school mathematics learning. Implementation of the CACAHSEWU worksheet with 11 students showed positive results, where the average student mastery in addition problems reached 76.4% and subtraction 50.9%, with an overall average of 63.6% in the good category. The 25.5% difference between addition and subtraction abilities indicates that subtraction operations with borrowing techniques remain a major challenge for grade IV students. From the motivation aspect, 81.8% of students stated they were more interested in learning mathematics with local cultural contexts, and 63.6% became more aware of the importance of preserving local culture. Error analysis revealed that 72.7% of students experienced difficulties in the borrowing process, and 81.8% struggled with consecutive borrowing. Ethnomathematics learning based on Batik Obor Sewu proved effective in increasing student motivation and conceptual understanding, but needs to be combined with adequate procedural practice, especially for subtraction operations. This research makes an important contribution to Indonesian ethnomathematics literature by demonstrating that local wisdom can be an effective bridge between formal mathematics and students' real-life contexts, while preserving cultural heritage for the younger generation.